Increased carbon dioxide concentration in the air reduces the severity of Ceratocystis wilt in Eucalyptus clonal plantlets - Santos, M. de S. dos [UNESP]; Ghini, R.; Fernandes, B. V.; Silva, C. A. (Springer, 2013)
The increased atmospheric carbon dioxide concentrations expected in the coming decades will result in changes in host-pathogen interactions. The present study aimed to evaluate the effect of high concentrations of CO2 in the air on the development of Ceratocystis wilt in two Eucalyptus clones (a hybrid of Eucalyptus urophylla and a cross between E. urophylla x E. camaldulensis). The clonal plantlets were cultivated under CO2 concentrations of 394 +/- 10 mu mol/mol (environmental condition), 553 +/- 15 mu mol/mol and 878 +/- 70 mu mol/mol in a controlled environment for 70 days and inoculated with Ceratocystis fimbriata conidia. In the treatments with 553 and 878 mu mol/mol, the plants of both clones had greater growth (215 % and 219 % increases in leaf area and 22 % and 24 % in stem diameter, respectively), a longer incubation period (65 % for both CO2 concentrations) and less disease severity (48 % and 78 % reduction, respectively) on average compared with the plants cultivated at 394 mu mol/mol. The carbon content of the leaves was greater at the higher CO2 concentrations; however, there was no difference in the C content of the stems and roots. The nitrogen content of the leaves, stems and roots were lower in the environments with higher CO2 concentrations. The results show that an increased CO2 concentration can reduce the severity of Ceratocystis wilt and stimulate the growth of Eucalyptus clonal plantlets.
Keywords: CO2; Eucalyptus; Ceratocystis fimbriata; Climate change; Disease